고령 운전자의 안전한 운전을 위한 기능적 평가 요소에 대한 고찰 - 박소연(So-Yeon Park) (한국컴퓨터정보학회논문지, 2021)
본 연구는 노인운전자의 운전 면허를 갱신 할 때 필요한 추가 검사를 제안할 목적으로 실시되었다. 우리나라에서는 고령 인구가 빠르게 증가하면서 고령 운전자의 비율이 높아지고 있다. 전반적으로 교통사고율이 감소하고 있지만, 고령 운전자에서는 교통사고율과 교통사고로 인한 사망률이 증가하고 있다. 본 연구에서는 우리나라에서 실시하고 있는 고령 운전자의 운전면허 갱신 시실시하고 있는 검사와 교육을 알아보고 외국의 현황과 비교하여 필요한 검사를 알아보기 위해 시행했다. 운전능력과 관련된 신체기능은 크게 시각, 인지, 운동 및 체성감각의 세 영역에 대해 평가하는 것이 적절하지만, 현재 우리나라에서는 시각 중 시력만을 평가하고 있고, 인지 영역에서는경증 인지 손상은 알아볼 수 없는 MMSE-K와 시계 그리기 검사만을 진행하고 있다. 운전을 수행하는 운동능력에 대해서는 전혀 평가하고 있지 않다. 따라서 고령 운전자의 안전운전을 위해서는운전면허 갱신 시 실시하는 검사에 시각에서는 시야와 대조대비력 검사, 인지 기능에서는 경증인지장애를 구별할 수 있는 검사, 운동기능을 평가하기 위한 검사를 보완해야 할 것이다. This study aims to present the need to supplement the driver's license renewal test for elderly drivers. In Korea, the proportion of elderly drivers is increasing as the elderly population increases rapidly. Overall the traffic accident rate is decreasing but the traffic accident and death rate from traffic accidents are increasing in older drivers. In this study the assessments and education conducted when renewing the driver's license for elderly drivers conducted in Korea were conducted to find out the necessary tests compared to the current situation of foreign countries. Although it is appropriate to evaluate the three key functional areas of vision, cognition, motor and somatosensory, we currently evaluate visual acurity in vison area. While MMSE-K and Clock drawing tests are not recognizable for mild cognitive impairment in cognitive areas. The motor and somato sensory function to perform driving are not evaluated at all. Therefore for safe driving of older drivers, the test to be conducted during renewal of the driver's license will need to supplement that the visual field and contrast sensitivity in vision area, cognitive function from mild cognitive impairments, and the endurance, functional range of motion and proprioception in motor function area. KCI Citation Count: 0